Mecanización de las labores de fumigación en la industria de flores - Huertas, José Ignacio; Carlos F.; Esteban, Juan (Revista de Ingeniería, 1999)
Colombian flowers industry needs to automatize the fumigation labors. This kind of job is developed under bad condition against the operator, great quantity of water is used an it has problems in the uniformity aspersion. Besides operators health is in danger and environment problems due to pesticides use. For above mentioned problems and with the financial aid of ASOCOLFLORES, a new prototype machine has been designed and built which mechanizes fumigation labor. One 4 axis motion controller allows to set up the advance speed, pesticide quantity, drop size and aspersion system verticality